PROSPECTS FOR TRADITIONAL LIVESTOCK BREEDING OF POLISH RED CATTLE WITH THE AGREEMENT OF BIODIVERSITY PROTECTION: Polish Red cattle breeding – animal welfare and the nutritional value of beef - Korzekwa, Anna; Siemieniuch, Marta; Kaczmarczyk, Julia; Kordan, Władysław (Polish Journal of Natural Sciences, 2023)
Meat from conservation breeding programs receives higher scores for juiciness, texture and aroma. Polish Red cattle kept on low-input farms where livestock are raised extensively (pastured in summer and fed farm-made fodder in winter) and highly appropriate for breeding due to moderate productivity and the high quality of milk and meat. In the past, Polish native cattle breeds were extensively grazed to preserve bird habitats in the same ecosystem. The demand for beef from “grass-fed” cattle is on the rise because consumers have a growing interest in animal health and well-being, environmental sustainability, and meat products with a modified nutritional profile and lower fat content. Two-thirds of the energy supplied by feed is required to maintain body functions of cattle. Energy expenditure increases in response to both low and high temperatures that differ from the thermal optimum of each species. Cattle are sensitive to both heat and winter stress, and the maintenance of thermal homeostasis requires additional energy when animals are exposed to suboptimal temperatures. Therefore, to ensure high levels of animal welfare, the grazing of traditional native cattle breeds should be planned by calculating nutrient yields in pasture grass and basal diets, not only for cows, but also for other free-ranging herbivores.